Emerging treatment options to improve cardiovascular outcomes in patients with acute coronary syndrome: focus on losmapimod - Kragholm K; Newby LK; Melloni C (Dove Medical Press, 2015)
Kristian Kragholm, Laura Kristin Newby, Chiara Melloni Duke Clinical Research Institute, Duke University Medical Center, Durham, NC, USA Abstract: Each year, despite optimal use of recommended acute and secondary prevention therapies, 4%–5% of patients with acute coronary syndrome (ACS) experience relapse of ACS or other cardiovascular events including stroke, heart failure, or sudden cardiac death after the index ACS. The sudden atherosclerotic plaque rupture leading to an ACS event is often accompanied by inflammation, which is thought to be a key pathogenic pathway to these excess cardiovascular events. Losmapimod is a novel, oral p38 mitogen-activated protein kinase (MAPK) inhibitor that targets MAPKs activated in macrophages, myocardium, and endothelial cells that occur as a part of global coronary vascular inflammation following plaque rupture. This review aims to 1) discuss the pathophysiological pathways through which p38 MAPKs may play key roles in initiation and progression of inflammatory disease and how losmapimod is thought to counteract these p38 MAPKs, and 2) to describe the efficacy and safety data for losmapimod obtained from preclinical studies and randomized controlled trials that support the hypothesis that it has promise as a treatment for patients with ACS. Keywords: p38 MAPK, p38 MAPK inhibitor, losmapimod, safety, efficacy, outcomes